Squamous cell carcinoma of the external auditory canal in a patient with non-resolving ear discharge - Nazli Zainuddin; Othman bin Abdullah (Malaysian Family Physician, 2015)
Discharging ear is a common symptom in the primary care and private general clinics. Most of the cases are treated with the antibiotic ear drops for otitis externa or otitis media. However, despite an adequate standard therapy, a malignant tumour can also be present with non-specific symptom such as ear discharge, especially in the case of persistent ear discharge. In this paper we have reported a case of an adult woman presented with non-resolving ear discharge who was treated repeatedly with antibiotic ear drop, which was later diagnosed as squamous cell carcinoma.